Implementasi Azas Peradilan Sederhana, Cepat, dan Biaya Ringan Perspektif Perma No. 3 Tahun 2022 Tentang Mediasi Secara Elektronik Terhadap Sengketa Wakaf dan Ekonomi Syariah di PA Lubuk Pakam - Sultan Khairul Fawaz; Fauziah Lubis (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This research aims to examine the application of simple,fast and light-cost principles through Supreme Court Regulation Number 3 of 2022 in adjudicating waqf and Islamic economic conflicts. The research problem centered on evaluating the effectiveness of electronic mediation implementation alongside identifying challenges encountered within religious judicial proceedings. This investigation was prompted by the necessity for an efficient justice system that adapts to technological progression while ensuring equitable access to legal remedies. The research methodology employed empirical-juridical approaches, integrating case analysis and regulatory assessment to examine the congruence between statutory provisions and their practical application in real-world settings. The findings demonstrated that technology-mediated mediation via e-court platforms can facilitate achieving simple, fast, and cost-efficient justice through optimization of temporal, financial, and administrative processes. Nonetheless, full implementation remains constrained by various barriers, including technological infrastructure deficiencies, digital literacy disparities, and human resource capacity limitations.